Growth of Devitrite, Na2Ca3Si6O16, in Soda–Lime–Silica Glass. Issue 5 (31st March 2014) - Knowles, Kevin M.; Thompson, Robert P.; Jantzen, C.
<x xml:space="preserve">Abstract</x> The morphology and crystal growth of devitrite crystals nucleated heterogeneously on glass surfaces have been studied. The crystals grow as fans of needles, with each needle having a characteristic [100] growth direction with respect to the centrosymmetric triclinic unit cell. An analysis of crystal growth data reported here and a reappraisal of crystal growth data reported in prior studies suggests a best estimate of 260 kJ/mol for the activation enthalpy for the crystal growth of devitrite along [100], higher than the values previously reported.